Fear in the fantastic narrative IT: a literary and cinematographic analysis - Araújo, Naiara Sales; Costa, José Antônio Moraes (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The present study aims to analyze the manifestation of fear in the fantastic narrative It, in both literature and cinema. Supernatural themes are a constant in fictional prose, providing an increase in studies on the relationship between fear and fantastic narratives. As theoretical support, we build on the literary scholarship of Yi-Fu Tuan (2005), Stephen King (2013), David Roas (2014), Marcel Martin (2003) and Jacques Aumont (2013). As for methodology, a content analysis model is adopted in a bibliographic, exploratory and qualitative approach. It, A novel, as a fantastic narrative, destabilizes our sources of security by questioning the validity of the systems and beliefs created by and imposed upon on humanity. The results illustrate how the fantastic genre has been characterized as presenting us phenomena and situations that signal a transgression of our reality. This rupture with the real is, therefore, a fundamen- tal effect of fantastic narratives which have also been explored in cinematic narratives.